(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In modern economic literature, the download speed of web resources is considered as a key indicator of the effectiveness of digital infrastructure and the level of economic development of the state. Increasing the capacity of Internet channels in all regions of Uzbekistan significantly affects macroeconomic indicators, stimulating productivity growth, attracting investment and strengthening the competitiveness of the national economy.